Colocutaneous fistula with recurrent urinary tract infection: a delayed complication following laparoscopic transabdominal pre-peritoneal repair - Kumar, Santhosh R.; Jayapal, Loganathan; Jebakumar, Gilbert S.; Muthaiah, Jeevanandham; Periyasamy, Samyuktha; Tasgaonkar, Siddesh S.; Kumar, Aishwarya M.; Prabhakaran, Raju; Swain, Sudeepta K.; Tiruporurgovindasamy, Balachandar (International Surgery Journal, 2023)
There has been an increase in incidence of delayed complications following transabdominal pre-peritoneal repair (TAPP) for inguinal hernia in the last two decades. Mesh related visceral complications (MRVCs) are difficult to diagnose and treat. Colocutaneous and colovesical fistualas are rare yet devastating delayed complications caused by mesh migration. We present the case of a 40-year-old man who presented to us after numerous hospital visits with urinary symptoms and a recurring fistula on the left abdominal wall at a previously operated site. Computed tomography revealed an ill-defined collection in left loin region abutting the sigmoid colon and urinary bladder. Owing to acute angulation, the colonoscope could not be passed beyond 30 cm. The patient was managed with cystoscopy, laparotomy, mesh explantation, and sigmoid colon resection.